Public policy and the social determinants of health: the challenge of the production and use of scientific evidence - Alberto Pellegrini Filho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
This article serves as an introduction to the others published in this thematic issue of the Cadernos de Saúde Pública. The author makes a brief historical review of the concepts, approaches and methodologies used to study the relationships between social determinants and health outcomes. By analyzing the current global movement around social determinants of health he emphasizes that the distinctive feature of this movement is the explicit commitment to action through intersectoral public policies that are based on evidence and implemented with the support and participation of broad segments of society. As this special issue of the Cadernos de Saúde Pública is dedicated to presenting the results of research related to social determinants of health, the author focuses on an analysis of the difficulties in the production and use of scientific evidence that supports the definition, implementation and evaluation of policies to combat health inequities through action on social determinants of health. To conclude, he presents some recommendations for overcoming these difficulties.